The Impact of Simulacra in Life Simulation Games “Second Life” on Generation Z’s Self-Confidence - Ramadhini, Diska Astari; Ratri, Dianing (Gorga : Jurnal Seni Rupa, 2025)
In the contemporary digital landscape, virtual environments have transcended their initial role as mere entertainment platforms into pivotal arenas for identity formation and self-expression. Notably, among Generation Z, digital natives raised in the midst of rapidly evolving technology, platforms such as Second Life provide immersive opportunities for the construction and live experience of digital avatars. These avatars often embody idealized versions of individuals, embodying characteristics or confidence that may be challenging to achieve in real-world interactions. This study delves into the impact of self-representation through avatars on self-confidence among Generation Z players. Adopting a descriptive qualitative approach, in-depth online interviews were conducted with five selected respondents. The analysis was guided by Jean Baudrillard’s theory of simulacra. The findings suggest that avatars initially serve as reflections of players’ identities but subsequently evolve into autonomous digital selves that shape behavior and perception. For many participants, engaging with their avatars fostered increased self-confidence and a sense of social ease within the virtual environment. However, the study also uncovered instances of emotional dissonance and psychological distance experienced by players who felt more authentic as their avatars compared to their real-life selves. These outcomes align with the third order of simulacra, hyperreality, where representation becomes a new reality. This research underscores the profound influence of virtual platforms on self-perception and emphasizes the necessity for a comprehensive interdisciplinary exploration of digital identity, particularly as younger generations continue to blur the boundaries between physical and virtual selfhood.